Representasi Seksisme Dalam Serial Drama Netflix The Queen’s Gambit Dari Pandangan Roland Barthes - Rifa Azahra; Maulana Rifai; Weni Adistyaning Arindawati (LPPM Stikosa - AWS, 2021)
The Queen's Gambit is a drama series that raises the issue of sexism against women, which in this drama is aimed at the character Beth Harmon. This study used a qualitative method with the semiotic approach of Roland Barthes. This study aimed to determine the meaning of denotation, connotation, and myths created about sexism in the drama series The Queen's Gambit. The scenes that became the object of the study consisted of 5 scenes that showed sexist behavior and speech. The results of this study indicate that women are depicted as creatures that are not smarter than men, are considered weak creatures, are objects made by the mass media to increase the market, are considered sexual objects, and are also considered troublesome for men.